Efeitos de escala em modelação numérica da erosão de um perfil de praia - Contente , J. (2012)
Scale effects in a numerical process-based beach profile model, applied to simulate beach profile evolution under erosive wave conditions, were investigated. The numerical model was applied at laboratory and prototype scales, first with the default settings and then calibrated. Its performance was evaluated using the Brier Skill Score. The numerical results of the profile evolution in both scales were compared after reducing the results from the prototype scale to the laboratory scale. The profile erosion prediction was overestimated in the laboratory scale and underestimated in the prototype scale. Despite the calibration parameter that causes the largest modifications of the beach profile being the same in both scales, the most efficient parameter was different. For most of the calibration parameters, the value for the best case was not coincident in both scales. It was concluded that there are scale effects using the Litprof model.